USE OF SAFETY BARRIERS IN THE PREPARATION OF VASOACTIVE DRUGS AND SEDATIVES/ANALGESICS IN PEDIATRIC INTENSIVE CARE - Carla Susana Martinez Julca; Patrícia Kuerten Rocha; Andreia Tomazoni; Bruna Figueiredo Manzo; Sabrina de Souza; Jane Cristina Anders (Universidade Federal do Paraná, 2018)
Objective: to analyze the use of safety barriers in the preparation of vasoactive drugs and sedatives/analgesics. Method: quantitative study, with 204 observations during the preparation of medications in a Pediatric Intensive Care Unit in the Pediatric Hospital of the State of Santa Catarina, between March 2016 and May 2017. The barriers analyzed were: type of prescription; transcription of the medication, identification of the patient and data on the label; label attachment; double checking; preparation of continuous infusions; and interruptions. The data were analyzed using descriptive statistics. Results:the safety barriers were related to written prescription (93.6%); transcription of the medication on the label (87.7%); patient identification on the label only by the first name (96%); data relating to the medication on the label failing to include the transcription of the route of administration (99.4%); double checking (34.6%); and interruptions during the preparation (52.9%). Conclusion: this study alerts the area to the need to implement barriers so as to promote safe clinical practice.